2018
DOI: 10.1016/j.jss.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensionally printed bioactive ceramic scaffold osseoconduction across critical-sized mandibular defects

Abstract: 3D-printed bioactive ceramic scaffolds can restore critical mandibular segmental defects to levels similar to native bone after 8 weeks in an adult rabbit, critical sized, mandibular defect model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
121
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 43 publications
2
121
0
Order By: Relevance
“…Previously prepared, calcined and milled, β‐TCP (Product 21218, Lot 1305078; Sigma‐Aldrich, St. Louis, MO) powder was utilized to fabricate the 100% β‐TCP colloidal gel suspension. The colloidal gel was fabricated with a solids volume fraction of approximately 46%, (ϕ solids = ~0.46), the detailed gel fabrication process can be found in previous work by Lopez et al and Tovar et al…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously prepared, calcined and milled, β‐TCP (Product 21218, Lot 1305078; Sigma‐Aldrich, St. Louis, MO) powder was utilized to fabricate the 100% β‐TCP colloidal gel suspension. The colloidal gel was fabricated with a solids volume fraction of approximately 46%, (ϕ solids = ~0.46), the detailed gel fabrication process can be found in previous work by Lopez et al and Tovar et al…”
Section: Methodsmentioning
confidence: 99%
“…Current in vivo investigations of 3D‐printed (3DP) scaffolds osseoconductivity have resulted in modest regenerative outcomes . Recent work by our group produced results supporting the use of 3D‐printed β‐tricalcium phosphate (β‐TCP) scaffolds for the repair of a critical‐sized (CSD) bony defect yielding new bone comparable with that of native bone . Despite these advancements, future studies are warranted to explore the potential of scaffolds augmented with bioactive molecules capable of exerting osteogenic effects as they may prove to be more of greater utility than uncoated β‐TCP scaffolds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A small but growing body of work has begun to demonstrate the effects of localized adenosine receptor activation via 3D printed, geometrically tailored osseoconductive scaffold carriers. Our group reported the first successful deployment of a bio‐ceramic scaffold with deliberate geometric design in a translational model (Lopez et al, ): by regeneration of a critical‐sized, full‐thickness mandibulectomy defect in a skeletally mature rabbit model. We demonstrated that bridging bone formation at the mandibular body could be achieved at eight weeks in vivo, even without osteogenic agents.…”
Section: The Integration Of Tissue Engineering Principlesmentioning
confidence: 99%
“…By manipulating these geometric levels, stages of both early and late bone healing can be altered to maximize new bone formation. These principles have recently demonstrated robust healing capacity at large bony defects when applied to calcium-phosphate based bio-ceramics (Bekisz et al, 2017;Ishack, Mediero, Wilder, Ricci, & Cronstein, 2015;Lopez et al, 2018;Simon et al, 2007).…”
Section: D Printing and Tissue Engineering: Essential Geometric Consmentioning
confidence: 99%